Scientific evidence of sodium-glucose cotransporter-2 inhibitors for heart failure with preserved ejection fraction: an umbrella review of systematic reviews and meta-analyses - Li, Runmin; Dai, Guohua; Guan, Hui; Gao, Wulin; Ren, Lili; Wang, Xingmeng; Qu, Huiwen (Frontiers in Cardiovascular Medicine, 2023)
Background It remains controversial whether sodium-glucose cotransporter-2 inhibitors (SGLT-2is) are effective in treating heart failure with preserved ejection fraction (HFpEF). Purpose The objective of this umbrella review is to provide a summary of the available evidence regarding the efficacy and safety of SGLT-2is for the treatment of HFpEF. Methods We extracted pertinent systematic reviews and meta-analyses (SRs/MAs) from PubMed, EMBASE, and the Cochrane Library that were published between the inception of the database and December 31, 2022. Two independent investigators assessed the methodological quality, risk of bias, report quality, and evidence quality of the included SRs/MAs in randomized controlled trials (RCTs). We further evaluated the overlap of the included RCTs by calculating the corrected covered area (CCA) and assessed the reliability of the effect size by performing excess significance tests. Additionally, the effect sizes of the outcomes were repooled to obtain objective and updated conclusions. Egger's test and sensitivity analysis were used to clarify the stability and reliability of the updated conclusion. Results This umbrella review included 15 SRs/MAs, and their methodological quality, risk of bias, report quality, and evidence quality were unsatisfactory. The total CCA for 15 SRs/MAs was 23.53%, indicating a very high level of overlap. The excess significance tests did not reveal any significant results. Our updated MA demonstrated that the incidence of the composite of hospitalization for heart failure (HHF) or cardiovascular death (CVD), first HHF, total HHF, and adverse events as well as the Kansas City Cardiomyopathy Questionnaire Total Symptom Score (KCCQ-TSS) and 6 min-walk distance (6MWD) were all substantially improved in the SGLT-2i intervention group compared to the control group. However, there was limited evidence that SGLT-2is could improve CVD, all-cause death, plasma B-type natriuretic peptide (BNP) level, or plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) level. Egger's test and sensitivity analysis proved that the conclusion was stable and reliable. Conclusions SGLT-2 is a potential treatment for HFpEF with favourable safety. Given the dubious methodological quality, reporting quality, evidence quality, and high risk of bias for certain included SRs/MAs, this conclusion must be drawn with caution. Systematic Review Registration https://inplasy.com/, doi: 10.37766/inplasy2022.12.0083, identifier INPLASY2022120083.